Crystal structure of bis(μ2-acetato-κ2O:O′)-bis{μ2-4-chloro-2-(8-(4-(diethylamino)-2-oxidophenyl)-3,6-dioxa-2,7-diazaocta-1,7-dien-1-yl)phenolato-κ6O:O,N,N′,O′′:O′′}tricobalt(II), C44H49Cl2Co3N6O12 - Yang Yu-Hua; Wang Bao-Jun; Lan Peng-Fei; Dong Wen-Kui (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C44H49Cl2Co3N6O12, Triclinic, P1̅, a = 9.7415(9) Å, b = 13.6440(14) Å, c = 17.5241(11) Å, α = 72.807(10)°, β = 83.019(9)°, γ = 72.246(9)°, V = 2450.6(5) Å3, Z = 2, Rgt(F) = 0.0700, wRref(F2) = 0.1505, T = 291(2) K.